Corporate governance of open and distance learning (ODL) institutions: special reference to Open University Malaysia - Zuhairah Ariff, Abd Ghadas; Tuan Fatma, Tuan Sulaiman (2018)
Corporate governance refers to a system that controls the relationship between the company (board of directors / director/ management team) and stakeholders. The corporate failures of Enron, Arthur Andersen, Worldcom, Parmalat, Kirch, Grand Tibidabo, Royal Dutch Shell and many others are claimed to be related to weak or lack of corporate governance. In the private education industry, open and distance learning (ODL) method have become increasingly popular. In Asia itself, there are seven out of eleven mega universities (universities with over 100,000 active students in degree-level courses) in the world. These include Allama Iqbal Open University, Pakistan, Open University of China, Indira Gandhi National Open University, Sukhothai Thammathirat Open University, Thailand, Universitas Terbuka, Indonesia, and Korea National Open University. In Malaysia, ODL is also offered by the private universities such as the Open University Malaysia (OUM), Wawasan Open University (WOU), Universiti Tun Abdul Razak (UNIRAZAK) and Asia eUniversity (AeU). Different from most of the public universities which are not a body corporate, all ODL institutions in Malaysia are companies and therefore subjected to good and proper corporate governance for sustainability of the business. This paper examines the corporate structure of ODL institution with special reference to OUM, which is the first ODL institution in Malaysia. The main objective of this paper is to analyse the governance framework which is applicable to ODL institutions. The research methodologies adopted by this paper are doctrinal and statutory analysis.